2020
DOI: 10.1553/moegg161s251
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the Relationship between Environment and Tourism: Case Study of the National Park Đerdap in Serbia.

Abstract: quently analysed approaches and the motivational basis for visiting can show how much the protected nature and healthy environment matter to the tourists. Based on the internal motivators, we examined whether the tourism in Đerdap is controlled, on a smaller scale, and qualitatively focused. A total of 484 respondents participated in the survey research. The comparison of attitudes was performed in relation to the demographic attributes of the respondents (gender, age, education). Target groups of tourists who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
4
0
2
Order By: Relevance
“…They are consistent with the studies of Bichler, Pikkemaat, & Peters (2020), which indicate that there is a direct positive relationship between the environment of a destination and the destination image as the environment generally incorporates every aspect of the location and acts as a collective for the area. Pavlović et al (2019) iterate that mindful use of environmental factors, especially in terms of sustainable approaches like creating accessibility, further cement the destination in tourists' eyes. Subsequently, they have an elevated view of the location.…”
Section: Discussionmentioning
confidence: 99%
“…They are consistent with the studies of Bichler, Pikkemaat, & Peters (2020), which indicate that there is a direct positive relationship between the environment of a destination and the destination image as the environment generally incorporates every aspect of the location and acts as a collective for the area. Pavlović et al (2019) iterate that mindful use of environmental factors, especially in terms of sustainable approaches like creating accessibility, further cement the destination in tourists' eyes. Subsequently, they have an elevated view of the location.…”
Section: Discussionmentioning
confidence: 99%
“…The residents emphasized the need for enriching the tourist offer, greater involvement of the local population and enhancements in the management of the protected area, through a focus on educating young people in the field of sustainable tourism. The researchers Pavlović et al (2020) observed motivational factors for tourists to visit DJNP such as new experiences and events, relaxation, the acquisition of new knowledge related to cultural and educational motivation, and the creation and realization of tourist products. They concluded that local self-government, residents and relevant institutions should be integrated so that the basic principles of sustainability are applied in practice.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Претходна истраживања српског екотуризма су првенствено била усмерена ка атракцијској основи и другим елементима туристичке понуде (Dolinaj et al, 2009;Stankov et al, 2011;Čučulović et al, 2012;Belij et al, 2016;Kalenjuk et al, 2016;Stojanović & Pavić, 2016). Мањи број истраживања је био усмерен ка вези између развоја екотуризма и локалних заједница (Stojanović et al, 2014;Brankov et al, 2015), другим интересним странама (Stamenković et al, 2016) и одликама тражње у екотуризму, попут задовољства (Belij, 2017) и мотивације (Pavlović et al, 2020). Већина ових студија је била усмерена ка покрајини Војводини као целини или конкретним дестинацијама у њој, са изузетком Stankov et al 2011 Светски еколошки покрет је остварио приметан раст популарности код младих људи у протеклим годинама, што их чини посебно значајним сегментом екотуристичке тражње.…”
Section: уводunclassified
“…Dolinaj et al, 2009;Stankov et al, 2011;Ĉuĉulović et al, 2012;Belij et al, 2016;Kalenjuk et al, 2016;Stojanović & Pavić, 2016). Smaller number of studies focused on the relationship between ecotourism development and local communities (Stojanović et al, 2014;Brankov et al, 2015), other stakeholders (Stamenković et al, 2016) and characteristics of the ecotourism demand, such as satisfaction (Belij, 2017) and motivation (Pavlović et al, 2020). The majority of these studies focused on the Vojvodina province in general or its particular destinations, with the exception of Stankov et al (2011), which focused on Stara Planina Nature Park, and Brankov et al (2015) and Pavlović et al (2020), which both focused on the Đerdap National Park.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation